1991
DOI: 10.4141/cjas91-125
|View full text |Cite
|
Sign up to set email alerts
|

The effects of marbling level, electrical stimulation, and postmortem aging on the cooking and palatability properties of beef rib-eye steaks

Abstract: For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
6
16
2
Order By: Relevance
“…This was unexpected because the average difference in price premium between Canada Prime and Canada AAA can be as much as an additional $10 per hundred weight (cwt, centum weight) for carcasses graded Canada Prime (Jim 2012). Previous studies characterizing the instrumental properties and eating quality of Canadian beef with various degrees of marbling have also showed that the degree of marbling had no effect on cooked beef toughness (Hawrysh and Berg 1976;Jones et al 1991), in agreement with the results of the present study. The difference in WBSF between Canada AA LT steaks and Canada AAA and Prime LT steaks in the present study approached significance (P = 0.0993), however, and this result was supported by a negative correlation between WBSF and intramuscular fat content.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This was unexpected because the average difference in price premium between Canada Prime and Canada AAA can be as much as an additional $10 per hundred weight (cwt, centum weight) for carcasses graded Canada Prime (Jim 2012). Previous studies characterizing the instrumental properties and eating quality of Canadian beef with various degrees of marbling have also showed that the degree of marbling had no effect on cooked beef toughness (Hawrysh and Berg 1976;Jones et al 1991), in agreement with the results of the present study. The difference in WBSF between Canada AA LT steaks and Canada AAA and Prime LT steaks in the present study approached significance (P = 0.0993), however, and this result was supported by a negative correlation between WBSF and intramuscular fat content.…”
Section: Discussionsupporting
confidence: 83%
“…Prior to Tedford et al (2014), the most recent comparison of eating quality properties by Canada beef grade was performed by Hawrysh and Berg (1976), when marbling was not part of the Canadian beef grading system and A grades were separated by subcutaneous fat thickness. The effect of marbling level on cooking and palatability properties of Canadian beef rib-eye steaks was later described by Jones et al (1991), who found that degree of marbling had no effect on perception of tenderness or desirability but that both the sensory perception of juiciness and the proportion of acceptable steaks increased as the amount of marbling in the steak increased. Given that several studies have reported that meat tenderness is the most important quality trait for the consumer (Savell et al 1989;Verbeke et al 2010) and that consumers are willing to pay an increased price for guaranteed tender meat (Boleman et al 1997;Miller et al 2001;Platter et al 2003), understanding the specific meat quality characteristics of each of the Canadian beef quality grades in a current context will assist with differentiating Canadian beef in international markets where consumers are willing to pay additional money for beef with increased eating quality (Lyford et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Increased marbling has been associated with improved meat eating quality (Jones et al, 1991;Wheeler et al, 1994). While in the present study partial replacement of grass silage with maize silage increased carcass gain, marbling fat or estimated carcass fat content were not altered, which may explain the absence of an effect on instrumental measures of meat quality.…”
Section: Feed Intakecontrasting
confidence: 46%
“…At the phenotypic level, Jones et al (1991) reported that degree of marbling had no effect on initial or overall tenderness, flavour intensity or desirability, but steaks with slight or greater marbling levels were juicier (P<0.05) than those with traces of marbling. The percentage of unacceptable ratings for steaks, based on overall palatability, declined from 38.5% for traces of marbling to 23.7% for modest marbling levels.…”
Section: Relationship Between Marbling and Tendernessmentioning
confidence: 99%